Cultural change and Transculturality The construction of kichwa cultural identity in Colombia - Martínez Díaz, Vivian (Universidad de Chile. Programa Domeyko, 2014)
The Kichwas or Otavalos are an indigenous people culturally and historically linked to the city of Otavalo in Ecuador. These people incorporate practices of migration, trade and musical interpretation as a way of living, but also as a part of their cultural identity. The Kichwas have been defined as indigenous subjects in dynamics of cultural change. Indeed, this cultural change is due to daily practice of transnational migration. Since 1940, many Kichwas have migrated to Colombia in order to make commercial exchanges. Afterwards, the Kichwas have organized themselves as a colony in Bogotá, and later as an indigenous government institution named ‘Cabildo Indígena’. Across the political action of the Cabildo, an official history of migration and settlement of these indigenous people in Colombia was constructed. In this history, migration, trade, music, prestige, solidarity and companionship are legitimized as symbolic elements of Kichwa cultural identity. This legitimation is possible through narratives of ‘próceres’ and ‘pioneros’ that represent the settlement of the Kichwas in the city.